The prospect for reservoirs in the 21st century proceedings of the tenth conference of the BDS held at the University of Wales, Bangor on 9-12 September 1998 - Tedd, P. (Thomas Telford, 1998)
This book contains the proceedings of the tenth biennial conference of the British Dam Society, held at the University of Wales in Bangor in 1998. Included are papers charting key issues on the future of dam engineering into the next century by eminent figures in the field of water engineering.